Quality and sensory attributes of tumbled or marinated beef jerky - McGinn, Ashton (Kansas State University, 2024)
Various methods are utilized by meat processors to make beef jerky. The most common methods utilized are tumbling or marinating meat. Each of these processing methods may influence jerky quality or sensory attributes. More research needs to be conducted to understand how these processing methods may affect the finished product. The objective of this research was to evaluate the quality and sensory characteristics of vacuum-packaged shelf stable beef jerky produced using tumbling or marination. Twelve USDA Select beef inside top rounds (semimembranosus) were held at 2℃ for 10 - 14 d before processing. On each processing day, whole rounds were trimmed, pH was measured, and the weights were recorded. Trimmed rounds were manually cut in half and each half was allocated to a tumbled or marinated treatment group. Before the treatments were applied, the beef round halves were sliced and weighed. Pieces from each half were held for moisture, fat, and protein determination, with separate samples allocated for transmission electron microscopy (TEM) and light microscopy (LM) to evaluate structural changes, sarcomere length (SL), and myofiber diameter (MD). After tumbling or marination, percent pickup was measured, and a piece from each half of tumbled or marinated rounds was held for sodium chloride content (SCC) analysis. Additionally, structural changes, SL, and MD were measured. After thermal processing, samples were sorted into groups based on storage periods of day 0, 3 months, or 6 months as well as calculating the percent cook yield. Analysis on day 0 consisted of measuring the pH, moisture, and protein content, moisture protein ratio (MPR), water activity (a[subscript w]), instrumental color, shear force (SF), trained sensory evaluation, SCC, structural changes, SL, and MD. Furthermore, vacuum-packaged jerky treatments stored for 3 and 6 months were analyzed for instrumental color, trained sensory evaluation, a[subscript w], SF, SCC, moisture content, structural changes, SL, and MD. Data was analyzed using a 3x2 factorial design where the fixed effects were the tumbled and marination processing methods of raw, raw tumbled, and raw marinated with storage periods at day 0, 3 months, and 6 months with individual rounds used as a random blocking factor. Sarcomere length and myofiber diameter results were analyzed separately based on the main effects of the treatment method. There were similar (P>0.05) results for the percent cook yield while the percent pickup was higher (P<0.05) for the tumbling process versus the marination process. Analysis of the moisture, fat, and protein content showed no differences (P>0.05) among treatment methods within raw top-round samples. After the tumbling and marinating process, there was no difference (P>0.05) in the SCC among the raw top-round slice samples. After the beef jerky was thermally processed, there were no differences (P>0.05) for pH, a[subscript w], protein content, MPR, or SCC. However, the moisture content was higher (P<0.05) in tumbled jerky than in marinated jerky which could be related to the increase in percent pickup during the tumbling process. The instrumental color values showed that L* values for tumbled beef jerky were lighter (P<0.05) in color and more red (P<0.05) in color for a* value than marinated jerky. Overall, jerky became darker (P<0.05) in color and more red (P<0.05) during storage. Shear force values were lower (P<0.05) in tumbled jerky with no change (P>0.05) over time. Sensory panelists found tumbled jerky to be less brittle (P<0.05), less chewy (P<0.05), and more flavorful (P<0.05) at day 0 and up to 6 months of storage at 20℃ compared to marinated jerky. Changes in structural integrity were observed due to processing methods and storage time. However, there was no difference between treatments or storage time for SL and MD. During storage, there was a decrease (P<0.05) in SCC over time and an interaction (P<0.05) with process treatment and storage time for b* value. All the other variables of a[subscript w], SF, moisture, and MPR were similar (P>0.05) for processing method and storage time. Overall, tumbling produced a jerky product that was more tender, less brittle, and more flavorful during 6 months of storage compared to marination as a processing method. Although tumbling yielded a higher percent pickup and jerky was darker in color than marinated jerky, the processing method did not influence SCC, a[subscript w], or MPR of beef jerky.
Keywords: Beef jerky; Tumble; Marinade; Microscopy; Sensory; Storage